TEACHING SPEAKING USIANG DIALOGUE: AN EFFORT TO ACTIVATE STUDENTS - Aquariza, Novi Rahmania (Universitas Nahdatul Ulama Surabaya, 2016)
Dialogue is well known as a way tointroduce an example of how to express something to the students. Dialogues are primarily used to provide speaking practice but can also develop listening. The teacher can use dialogues to introduce and practice a function, structure, or vocabulary, and to illustrate degrees of politeness, levels of formality, and attitudes of the target culture. Moreover, students can be more activebecause of it. The writer assumes that though the students with less vocabulary still can speak and feel well in front of their other classmates because standard dialogue provide many vocabularies and expressions to be used. There are many types of dialogue; most of them are interesting to be used in an English class. In this paper, the writer tries to present an idea that dialogue in some types are not only good and effective to be used, but also able to activate the students, especially in a speaking class.